Surface application of fertilizers and residue biochar on N2O emission from Japanese pear orchard soil - Aung Zaw OO; Takeru GONAI; Shigeto SUDO; Khin Thuzar WIN; Akira SHIBATA (Plant, Soil and Environment, 2018)
This study investigated soil N2O emissions following the application of fertilizers and pruning residue biochar on the soil surface of the Japanese pear orchard. Completely randomized design was laid out with four treatments: (1) control (unfertilized); (2) pig manure 300 kg N/ha and ammonium sulfate 200 kg N/ha with no biochar (F + BC0); (3) the same amount of manure and nitrogen (N) fertilizer with 2 t/ha biochar (F + BC2), and (4) with 10 t/ha biochar (F + BC10). The results showed that high N2O fluxes were observed after fertilization. Soil temperature and moisture were major controlling factors for N2O emission from the orchard soil. The lowest cumulative N2O emission (0.46 kg N/ha) was observed in the unfertilized control. Application of manure and N fertilizer significantly increased cumulative N2O emission compared to unfertilized control. Surface application of biochar (1.68 and 1.77 kg N/ha in F + BC2 and F + BC10, respectively) had no effect on soil N2O emission compared to F + BC0 (1.68 kg N/ha). Our results indicated that biochar pyrolyzed from orchard pruning residues can be returned to orchard soil as surface application without affecting soil N2O emissions.